GAMBARAN STATUS GINGIVA PADA PENDERITA LEUKEMIA DI RSUP PROF. DR. R. D. KANDOU MANADO - Suling, Pieter L.; Mintjelungan, Christy N.; Tangka’a, Roy R. B. (e-GiGi, 2015)
Abstract: Periodontal disease is a disease tooth and mouth the most common suffered. Bacterial plaque buildup on the surface of the tooth is the main cause of periodontal disease. Periodontal disease started from gingivitis, when untreated can develop into periodontitis where periodontal tissue damage occurs in the form damage of fibre, periodontal ligament, and alveolar bone. Leukemia is a malignancy disease characterized by the presence of bleeding. Location of bleeding most often found on the skin, eyes, nose mucous membrane, gingiva and gastrointestinal tract. The purpose of this research is to know the description of the status of gingiva in sufferers of leukemia in was Prof. Dr. r. d. Kandou Manado.This was descriptive study with cross sectional approach. Samples was collected using total sampling by examination the status of gingiva based on index gingiva Loe and Silness. The results showed that most of the patients experiencing mild inflammation (68,75%) and the rest suffered medium inflammation (31,25%). Based on age, puberty is largely experiencing mild inflammation (56,25%) and adolescents medium inflammation (18,75%). Based on the gender, men mostly experiencing mild inflammation (31,25%) and most women experience mild inflammation (37,50%). Based on the type of disease, LLA mostly suffered inflammation lightweight (68,75%), LMA all experiencing inflammation medium (6,25%) and LMK all experiencing inflammation medium (12,50%). Conclusion: Leukemia patients treated at Prof. Dr. R. D. Kandou had the awareness to maintain oral hygiene, however, socialization about the importance of oral hygiene is still needed.Keywords: leukemia, periodontal disease, gingival statusAbstrak: Penyakit periodontal merupakan penyakit gigi dan mulut yang paling umum diderita. Penumpukan bakteri plak pada permukaan gigi merupakan penyebab utama penyakit periodontal. Penyakit periodontal dimulai dari gingivitis, bila tidak terawat bisa berkembang menjadi periodontitis dimana terjadi kerusakan jaringan periodontal berupa kerusakan fiber, ligamen periodontal dan tulang alveolar. Leukemia merupakan penyakit keganasan yang ditandai dengan adanya perdarahan. Lokasi perdarahan yang paling sering ditemukan pada bagian kulit, mata, membrane mukosa hidung, gingiva dan saluran cerna. Tujuan penelitian ini ialah untuk mengetahui gambaran status gingiva pada penderita leukemia di RSUP Prof. Dr. R. D. Kandou Manado. Penelitian ini bersifat deskriptif dengan pendekatan cross sectional. Pengambilan sampel menggunakan metode total sampling dengan cara melakukan pemeriksaan status gingiva berdasarkan indeks gingiva Loe dan Silness. Hasil penelitian menunjukkan bahwa sebagian besar pesien mengalami inflamasi ringan (68,75%) dan sisanya mengalami inflamasi sedang (31,25%). Berdasarkan umur, pubertas sebagian besar mengalami inflamasi ringan (56,25%) dan remaja mengalami inflamasi sedang (18,75%). Berdasarkan jenis kelamin, laki - laki sebagian besar mengalami inflamasi ringan (31,25%) dan perempuan sebagian besar mengalami inflamasi ringan (37,50%). Berdasarkan jenis penyakit, LLA sebagian besar mengalami inflamasi ringan (68,75%), LMA semuanya mengalami inflamasi sedang (6,25%) dan LMK semuanya mengalami inflamasi sedang (12,50%). Simpulan: Pasien leukemia yang berada di RSUP Prof. Dr. R. D. Kandou memiliki kesadaran untuk menjaga kebersihan mulut, tetapi sosialisasi tentang pentingnya menjaga kebersihan gigi dan mulut masih dibutuhkan.Kata kunci: leukemia, penyakit periodontal, status gingiva.